Correlative polarizing light and scanning electron microscopy for the assessment of talc in pelvic region lymph nodes. (2nd January 2019) - McDonald, Sandra A.; Fan, Yuwei; Welch, William R.; Cramer, Daniel W.; Stearns, Rebecca C.; Sheedy, Liam; Katler, Marshall; Godleski, John J.
ABSTRACT: Perineal talc use is associated with ovarian carcinoma in many case-control studies. Such talc may migrate to pelvic organs and regional lymph nodes, with both clinical and legal significance. Our goal was to differentiate talc in pelvic lymph nodes due to exposure, versus contamination with talc in the laboratory. We studied 22 lymph nodes from ovarian tumor patients, some of which had documented talc exposure, to quantify talc using digestion of tissue taken from paraffin blocks and scanning electron microscopy/energy dispersive X-ray analysis (SEM/EDX). Talc particles correlated significantly with surface contamination assessments using polarized light microscopy. After adjusting for surface contamination, talc burdens in nodes correlated strongly with perineal talc use. In a separate group of lymph nodes, birefringent particles within the same plane of focus as the tissues in histological sections were highly correlated with talc particles within the tissue by in situ SEM/EDX (r = 0.80; p < 0.0001). We conclude that since talc can be a surface contaminant from tissue collection/preparation, digestion measurements may be influenced by contamination. Instead, because they preserve anatomic landmarks and permit identification of particles in cells and tissues, polarized light microscopy and in situ SEM/EDX are recommended to assess talc in lymph nodes.